Implementation of E-marketing in the Restaurant Sector in Butwal Sub-Metropolitan City, Butwal, Nepal - Rana, Bikash; Dhakal, Narayan Prasad; G.C., Prakash (Kalika Journal of Multidisciplinary Studies, 2025)
Small and medium-sized restaurants (SMRs) in semi-urban regions such as Butwal are navigating both opportunities and challenges in the adoption of e-marketing strategies as digital technology reshapes Nepal’s business landscape. This study examines the primary factors influencing the utilization of digital marketing tools by these companies, focusing on organizational capability, technological readiness, and external market conditions. The research employs the Technology Organization Environment (TOE) framework and analyzes data from 384 Small and Medium- sized Enterprises (SMEs) in Butwal, pinpointing advantageous market conditions and the perceived benefits of e-marketing as the principal factors influencing digital adoption. On the other hand, things like trialability, compatibility with existing systems, and customer pressure are of lesser significance. The results unequivocally illustrate a correlation among improved customer engagement, brand visibility, overall marketing performance, and the effective utilization of e- marketing. Despite these advantages, several SMRs continue to face challenges such as insufficient internal expertise, a deficiency in strategic planning, and a fragile digital infrastructure. This study underscores the necessity for targeted training, enhanced infrastructure, and policies tailored to the needs of businesses functioning outside major urban areas, offering valuable insights for policymakers, advocacy organizations, and local entrepreneurs. The study highlights the importance of aligning digital tools with local business realities to promote sustainable growth in Nepal’s evolving hospitality sector.